Branched and linear A2–D–A1–D–A2 isoindigo-based solution-processable small molecules for organic field-effect transistors and solar cells1. Issue 104 (11th November 2015) - Tomassetti, Mirco; Ouhib, Farid; Cardinaletti, Ilaria; Verstappen, Pieter; Salleo, Alberto; Jérôme, Christine; Manca, Jean; Maes, Wouter; Detrembleur, Christophe
<x xml:space="preserve">Abstract</x> A2–D–A1–D–A2 type small molecules were synthesized, providing a solar cell efficiency of 1.9% and hole mobility of 3.7 × 10−3 cm2 V−1 s−1.